Acoustic signal of Obolopteryx eurycerca Barrientos-Lozano y Rocha-Sánchez (Orthoptera: Tettigonidae: Phaneropterinae) - Salinas-Dosal, Hillary G.; Barrientos-Lozano, Ludivina; Rocha-Sánchez, Aurora Y.; Almaguer-Sierra, Pedro; González-Gaona, Othón J. (Instituto de Ecología, A.C., 2023)
In Ensifera (Tettigoniidae: Phaneropterinae), males produce acoustic signals through tegminal stridulation; these signals act primarily to attract sexually receptive conspecific females for mating. The study of bioacoustics is also a complementary tool in traditional morphological studies since these signals are species-specific and allow the differentiation of morphologically similar (cryptic) taxa. Acoustic signals represent an important intra and interspecific communication system. Members of the family Tettigoniidae are remarkable for producing acoustic signals that are frequently inaudible to the human ear [frequency (f) > 20 kHz]. Although Mexico is endowed with an extensive diversity of insects, few studies have focused on their acoustic repertoire. In this work, we describe for the first time, the ultrasonic acoustic calling signal of Obolopteryx eurycerca Barrientos-Lozano & Rocha-Sánchez, 2016. The specimens studied were collected in the municipality of Hidalgo, Tamaulipas, Mexico. The males’ calling signal is made up of echemes of three syllables, emitted in a continuous fashion for long periods of time (± 1h). The acoustic signal of O. eurycerca is compared with that of O. castanea (Rehn & Hebard, 1914) and the advantages of ultrasonic acoustic communication in Ensifera are discussed.